Healthcare resource utilization in adult patients with relapsed/refractory FLT3 mutated acute myeloid leukemia: A retrospective chart review from Spain. (5th March 2021) - Solana‐Altabella, Antonio; Boluda, Blanca; Rodríguez‐Veiga, Rebeca; Cano, Isabel; Acuña‐Cruz, Evelyn; Blanco, Albert; Marco‐Ayala, Javier; de la Puerta, Rosalía; Díaz‐González, Álvaro; Piñana, José L.; Sanz, Jaime; Sempere, Amparo; et al.
Abstract: Background: Information regarding impact on healthcare systems of relapsed or refractory (R/R) FLT3 mutated ( FLT3mut ) acute myeloid leukemia (AML) is scarce. Objective: To assess the time and reimbursement associated with hospitalizations of patients with R/R FLT3mut AML in a tertiary Spanish hospital. Methods: Retrospective review of medical charts identified patients aged ≥ 18 years with R/R FLT3mut AML between 1998 and 2018. Data were collected from the date of first diagnosis of R/R FLT3mut AML (index) until death or loss to follow‐up. The primary end point was duration and frequency of hospitalization, use of outpatient resources and transfusion burden. Reimbursement associated with hospitalizations (including associated chemotherapy) was also assessed. Results: Thirty‐eight patients were eligible for inclusion. Their median age was 52 years, and 30 (79%) received intensive salvage chemotherapy; FLAG‐IDA‐based regimens were the most frequent (24 patients, 63%). Overall, there were 150 hospitalizations (mean 3.9/patient; mean duration 21 days). Patients spent a mean of 24% of the study period in hospital. Total mean reimbursement was €108 293 per patient; the majority (€89 834) attributable to inpatient stays (€22 576 /hospitalization). During chemotherapy period (prior to first alloHSCT), there were 73 hospitalizations (mean duration 22 days); mean reimbursement was €19 776 per hospitalization and €49 819 per patient. AlloHSCT (n = 16) involved 77 hospitalizations (mean duration 21 days), mean reimbursement €25 231/hospitalization and €131 515 per patient. Conclusion: Data from this study suggest that there is a substantial healthcare resource utilization and cost burden on R/R FLT3mut AML patients in Spain receiving active treatments.